The formation of desilication products in the presence of kaolinite and halloysite – The role of surface area - Gomes, Jose F.; Davies, M.; Smith, P.; Jones, Franca (ELSEVIER, 2021)
A great deal of effort has been dedicated to improve the fundamental understanding of the mechanism of desilication product crystallization under Bayer process refinery conditions. Differences in the mineralogy of the reactive silica found in bauxite could change the kinetics and possibly the formation pathways of the desilication product. In this work, halloysite was investigated and compared to kaolinite, which is commonly found in bauxite. Different ratios of kaolinite and halloysite were used to form desilication product and the solids formed were characterized thoroughly to determine the impact the presence of the clay had. In addition, differences in dissolution rate due to the presence of halloysite was determined. The results show that the presence of halloysite led to a faster dissolution rate of the clay overall, which can be attributed to the total specific surface area of the reactive silica source. Thus, the crystallinity of the clay was found to have limited impact. The presence of halloysite also increased the measured maximum solution [SiO2] in solution, which in turn increases the driving force for the formation of desilication product. The increase in halloysite content thus results in desilication product being observed at an earlier stage and, overall, leads to an enhanced rate of desilication product formation.